Application of Health Belief Model on Breast Self-Examination: A Meta-Analysis - Maranata Maranata; Eti Poncorini Pamungkasari; Rita Benya Adriani (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Breast cancer is a type of cancer and the leading cause of cancer death in women. BSE is an early detection method for breast cancer. Health Belief Model is a model of health behavior that can predict women's interest in practicing BSE. This study aims to estimate the Health Belief Model's effect in the practice of BSE by meta-analysis.Subjects and Method: Meta-analysis was performed by searching for articles from the PubMed database, Springer Link, Elsevier, and Google Scholar. The keywords used were